The Impact of Racial Representation on Judicial Legitimacy: White Reactions to Latinos on the Bench. (March 2023) - Achury, Susan; Casellas, Jason P.; Hofer, Scott J.; Ward, Matthew
Despite evidence that racial diversification has increased support for the judiciary, political scientists know little about the heterogeneous effects of diversification across different population segments. Previous research illustrates that including Black judges increases judicial legitimacy among the Black population, but it decreases the legitimacy of the courts among the White population. We expand on this knowledge by examining the impact of adding Latinos to the bench. Our survey experiment compares White respondents' perception of the courts based on differing levels of Latino representation in the ruling panel. Does descriptive representation in the racialized issue area of immigration signal fairness and legitimacy to White respondents? Or does the inclusion of Latino jurists in immigration cases trigger racial animosity and decreasing support for the courts? We find that when the court rules against the White respondent's preference, they tend to penalize all-White judicial panels that rule against the perceived interest of Latinos. Additionally, we find that when presented with a Latino majority panel, White respondents who disagree with the ruling are more likely to punish the anti-Latino decisions as their levels of group consciousness increase. Ultimately, our findings illustrate how judicial diversity may affect the countermajoritarian capacity of the judiciary.